Peningkatan Keterampilan Menulis Hasil Wawancara Peserta Didik Melalui Metode Outdoor Study - Mirva Faudati; Siti Rochmiyati (Jurnal PGSD, 2023)
The objective of this study was to enhance students' proficiency in documenting interview outcomes through the application of outdoor study methods. The participants were 10 students selected from an elementary school in Kapanewon Samigaluh, Kulon Progo Regency, comprising 6 boys and 4 girls. The research utilized a classroom action research approach. The findings indicated a progressive improvement in students' ability to write down interview results in each cycle. During the initial cycle, students achieved an average score of 11.1 with a success rate of 50%, which falls within the category of "good" (category B). In the second cycle, the score increased to 13 with a success rate of 60%, still classifying as "good" (category B). The third cycle saw a further surge, with the average score reaching 15.7 and a success rate of 80%, placing it in the "very good" (SB) category. These results lead to the conclusion that employing outdoor study techniques contributes to the enhancement of students' writing skills in documenting interview results.